Legal Protection for Persons with Disabilities in Specific Time Working Agreements - Mohamad Adya Laksmana Sudradjat; Faisal Santiago (Journal of Social Research, 2023)
Law Number 8 of 2016 concerning Persons with Disabilities, explains that persons with disabilities are any person who experiences physical, intellectual, mental, and/or sensory limitations in interacting with the environment and other citizens experiencing obstacles and difficulties to participate fully and effectively. In the employment relationship between the company and the workforce, in this case, the problem solver is a promise of work. The work agreement is the basis for the formation of a working relationship. An employment agreement is valid if it fulfills the legal requirements of the agreement and the legal principles of the engagement. In the event that it is made in writing, it must pay attention to the applicable laws and regulations, for example, it regulates work agreements for a certain time. Fixed time work agreement. The problem is how is the legal protection for persons with disabilities in a work agreement for a certain time? Normative juridical and empirical juridical research methods. The perfection is that legal protection for people with disabilities in work agreements for a certain time is adjusted to the needs of the company which is carried out through requirements that have been stipulated in a separate decree, while still observing the applicable company laws and regulations and company laws and regulations. This can be seen from the lack of employee disturbance, such as at PT. Pupuk Indonesia the number of disruptive employees is 24 people, in terms of facilities PT. Pupuk Indonesia has prepared additional facilities for disruptive employees.